Comparative Perception Among Minority Communities on the Knowledge of UN Convention of the Rights of Child, Institutional Responsibilities and Child Participation in Decision Making Processes - Zeqiraj, Nehare (European Journal of Multidisciplinary Studies, 2016)
The survey document is mandated to address two issues in Republic of Kosova as following: I. Knowledge, Attitude and Practices of children and communities in relation to children rights and child protection in 5 Kosovo regions: Peja Gjakova, Ferizaj, Prizren and Fushe Kosovo II. Evaluation of the communities knowledge on existing services in case of violations of the children rights in 5 Kosovo regions: Peja Gjakova, Ferizaj, Prizren and Fushe Kosovo